Migraciones y desplazamientos forzados Nuevas aproximaciones y contribuciones al estudio de la migración contemporánea - Palomera, Adriana; Herrera, Simón (Ariadna Ediciones, 2021)
In recent decades, Chile has not been immune to the dynamics of increasing immigration, causing a strong impact on public opinion. In this scenario, we must add the closing of borders as a result of the pandemic and the security policies installed by some governments, leaving multiple groups of immigrants and refugees subject to greater defenselessness. This book is the result of the academic work of young researchers graduated from Analysts in Politics and International Affairs at the University of Santiago de Chile, who have found in human movements a place to develop their first approaches to research and who represent an interest in the theme of the new generations. In order to promote the work carried out by these young researchers in the migration area and to empower them, it is essential to disseminate their proposals with a publication like this one, making this objective one of the main purposes of this text.